Incommensurabilità interculturale, dialogo tra culture, ecologia dei saperi e métissages culturali - André, João Maria (Filosofia, 2015)
This paper opens with a brief contextualization of the current multicultural phenomenon, with a focus on the nation-state erosion, and on globalization and the network society. After a clarification of several ambiguous uses of the the word ‘multiculturalism’, this paper investigates the possibility of intercultural dialogue, taking into account the incommensurability (in the Kuhnian sense) that might characterize cultural relations. We then proceed to clarify the positions that some authors such as the Mexican Leon Olivé (plural cultural constructivism), German Ulrich Beck (multiple contextual universalism) and the Portuguese Boaventura de Sousa Santos (ecology of knowledge) take on these matters, and we outline the fecundity of the miscegenation/métissage concept as a response to the intercultural dialogue problematic as well as to the sociocultural notion of identity that the current multicultural society claims. We conclude by opening the possibilities of finding, in the artistic practices, a good tool to the effectiveness of cultural miscegenation and to a dynamic and fruitful intercultural dialogue.